Axial, flexural and torsional rigidities of two-dimensional braided fibre composite medical catheters - Carey, Jason (University of Ottawa (Canada), 2003)
The development of a one-piece braided model catheter with the same rigidities as the combined medical catheter-guidewire system presently employed during cardiovascular catheterization procedures is the principal goal of this research. This will result in a significant reduction in the time required to insert a cardiovascular catheter. This is also the first and fundamental step in the development of optimal rigidity cardiovascular catheters. To begin, the axial, torsional and flexural rigidities of existing medical catheters were reviewed and measured. A model to predict the longitudinal tensile and in-plane shear moduli of 2D braided structures, needed for the calculations of the axial, torsional and flexural rigidities of braided tubes, was developed. The sensitivity of the model to key constituent and laminar properties was analysed. It was concluded that accurate values of Efl1, E m and Gm are required for the micromechanical model; the model is not sensitive to the remaining elastic constants (nuf12, nu f23, Gfl2, G23). Oversized braided (Kevlar 49 fibre and thermoset matrix) engineering model composite structures---or model catheters---have been used to verify the model. These model catheters have been produced on an existing braiding machine. Kevlar 49 fibre and epoxy resin have been used primarily because the laminar mechanical properties have been measured in a previous experimental study by Flanagan and Munro [72]. There was good agreement (approximately 6%) between the predicted and measured values of the longitudinal elastic modulus of braided tubes which provided confidence in the model. Shear modulus predictions and the range of experimental results also showed reasonable agreement. The results also show that micromechanical models in which accurate values for important elastic constants (Ef11, Em and G m) are used can accurately predict the experimental results. The preceding experimental work was carried out for full coverage rigid thermoset matrix braided fibre composites. Actual medical catheters require flexible matrix and an open fibre mesh rather than full fibre coverage; therefore, it was necessary to select the appropriate matrix and reinforcement for an actual medical catheter. The proposed CLPT model was used to select the appropriate fibre and resin to obtain rigidities similar to those of the existing medical catheter-guidewire systems. Laminar elastic constants were estimated using micromechanical models. The proposed CLPT model reasonably predicted the longitudinal elastic and shear moduli of model catheters produced with one of the selected elastomeric resins. (Abstract shortened by UMI.)
Keywords: Engineering, Biomedical.; Engineering, Mechanical.